Participation of Healthy Volunteers in Clinical Trials - Motives, Barriers, and Ethical Issues - Raja Sajjad Asghar; Javeria Saleem; Muhammad Ishaq (BioMedica, 2023)
Recruitment of adequate number of healthy volunteers is vital for success of clinical trials but there is limited research on factors motivating the healthy volunteers to participate in clinical trials especially in developing countries. Pakistani researchers also faced the problems in enrollment of enough healthy volunteers during COVID-19 pandemic when a number of clinical trials began in Pakistan. Around 117 research proposals were processed by the National Bioethics Committee (NBC) of Pakistan in last two years. A major proportion of these clinical research studies target healthy populations as primary research subjects or as controls. Numerous studies have investigated factors such as motives, barriers, risks. benefits and ethical values affecting recruitment and participation of healthy volunteers in clinical trials. We have reviewed the literature to learn about factors that motivate or prevent the healthy persons to volunteer along with the pertaining ethical issues. Financial incentive is the principal motive for healthy volunteers to participate in clinical trials along with altruism, contribution to sciences, research and other people’s health, desire to take part in something important, learning more about science and medicine, access to healthcare & free medical checkup and prospects of one’s social network expansion whereas time inconvenience, confidentiality, possible side effects & route of administration of drug and fear of contacting the disease were identified as important barriers. Application of knowledge of these motives and barriers will help Pakistani researchers to enroll adequate number of healthy volunteer for their clinical trials.